Flowable Urethane Dimethacrylate-Based Filler for Root Canal Obturation in Primary Molars: A Pilot SEM and microCT Assessment - Saulius Drukteinis; Audra Drukteiniene; Lesbia Drukteinis; Luc C. Martens; Sivaprakash Rajasekharan (MDPI AG, 2021)
Pulpectomy in deciduous teeth involves endodontic access opening, root canal debridement and obturation with an appropriate filling material. EndoREZ (ER) is the urethane dimethacrylate-based filler, which can be used for root canal obturation in permanent and primary teeth. This observation aimed to evaluate the behavior of the ER as a filler in root canals of two primary molars after the physiological resorption process using the scanning electron microscopy (SEM) and micro-computed tomography (µCT) in second lower molars after their natural exfoliation. The SEM analysis revealed a non-uniform, porous and lacunary structure of ER, visually similar to the resorbed surface of the dentine. The µCT observations demonstrated the differences in the resorption level of the root and material surfaces. The preliminary observations suggest that ER is resorbed faster than root tissues and can therefore be a suitable material for the root canal filling in primary teeth. However, more investigations are needed to support these preliminary findings.